2011
DOI: 10.3892/ijmm.2011.770
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl isothiocyanate sensitizes human pancreatic cancer cells to radiation by inducing apoptosis

Abstract: Abstract.Isothiocyanates are a class of naturally occurring chemopreventive agents known to suppress proliferation of cancer cells in culture. The present study was undertaken in order to examine the effects of benzyl isothiocyanate (BITC), one of the common dietary isothiocyanates, on the radiosensitivity of human pancreatic cancer cells and to gain insights into the underlying molecular mechanism of BITC-induced radiosensitization. Two human pancreatic cancer cell lines, PANC-1 and MIAPaCa-2, were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…In fact, RT treatment alone led to significant increase in BCL2 levels (Figure 5, p<0.01), 13 and a trend to diminish BAX levels. Irradiated Mia PaCa-2 cells also changed their BAX to BCL2 balance in the same way (20), the control of BCL2 family member levels being known as a mechanism of RT resistance (29). Our result suggests that addition of BFCs to irradiation counteracts this resistance mechanism.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In fact, RT treatment alone led to significant increase in BCL2 levels (Figure 5, p<0.01), 13 and a trend to diminish BAX levels. Irradiated Mia PaCa-2 cells also changed their BAX to BCL2 balance in the same way (20), the control of BCL2 family member levels being known as a mechanism of RT resistance (29). Our result suggests that addition of BFCs to irradiation counteracts this resistance mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…Several BFCs radiosensitize tumor cells such as the polyphenols curcumin (18) and quercetin (19) or the sulfamide sulforaphane (20), for example. Considering our previous work on pancreatic tumor cell chemosensitization by combination of capsaicin and resveratrol (9), we tested the same approach with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In various reports have shown that radiation-induced apoptosis is enhanced by some agents such as apigenin, curcumin, genistein, sulforaphane, benzyl isothiocyanate, olaparib, rucaparib, elesclomol, 17-DMA, LY2603618, MK87776, and AZD1775, EphB4, human PLK1. [2327293233] Our observations are opposite of their results. However, in many studies such as Rafehi et al .,[34] clonogenic formation assay was introduced as the gold standard to investigate radiosensitizers.…”
Section: Discussioncontrasting
confidence: 99%
“…Many radiosensitizers that function at a cellular level have already been investigated. These include apoptosis-enhancing natural chemical components [1], chemicals which increase DNA damage resulting from radiation [2, 3], kinase inhibitors for ATM/ATR/Chk1/Chk2 [3], and PARP inhibitors [3], although these agents are not tumor tissue-specific sensitizers.…”
Section: Introductionmentioning
confidence: 99%